Mispronunciations in Graduate Students’ Presentation Projects - Yeskha Martika Megariani; Nadia Aprilia Listyantari; Barli Bram (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
This paper explored the mispronunciations produced by Indonesian graduate students in their presentation projects. The data were collected from presentation projects of 11 graduate students of the English Education Master’s Program of Sanata Dharma University. The researchers used a document analysis as a technique to analyze the data. Results showed that 89 mispronunciations existed in the presentation projects. The mispronunciations were categorized into three types of errors, namely: 26 mispronunciations belonged to the first type, the problems in the pronunciation of non-native sound; 36 mispronunciations belonged to the second type, the carry-over of pronunciation regularities from the mother tongue (L1); and 27 mispronunciations belonged to the third type, the overgeneralizations of target language (L2) regularities. It is expected that the findings can become a stepping stone for graduate students to improve their English pronunciation.